2016
DOI: 10.1007/s10068-016-0074-y
|View full text |Cite
|
Sign up to set email alerts
|

Quality characteristics of fermented sausage prepared with soy sauce

Abstract: The contributions of soy sauce to the quality characteristics of fermented sausages were investigated. The number of lactic acid bacteria in sausages prepared with soy sauce increased from the first day of fermentation, and the population reached approximately log 7 CFU/g by the 5 day of fermentation. The pH decreased sharply to 5.0-5.1 by the 5 day of fermentation, in accordance with the dramatic increase of titratable acidity. After 36 days of fermentation, the levels of total organic acids and amino acids i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
4
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(5 citation statements)
references
References 38 publications
1
4
0
Order By: Relevance
“…The organic acid of the patty stored for 10 days showed no significant difference or tendency to increase from the control (−) group of the patty stored for 0 days. The oxalic acid content reported in the present study was similar to the findings of a previous study [ 62 ]. The organic acid content between patties did not show a significant difference as a whole, but the oxalic acid content was high in patties with soy sauce.…”
Section: Resultssupporting
confidence: 92%
“…The organic acid of the patty stored for 10 days showed no significant difference or tendency to increase from the control (−) group of the patty stored for 0 days. The oxalic acid content reported in the present study was similar to the findings of a previous study [ 62 ]. The organic acid content between patties did not show a significant difference as a whole, but the oxalic acid content was high in patties with soy sauce.…”
Section: Resultssupporting
confidence: 92%
“…Kameník et al ( 2012 ) stated that initial pH in vacuum packed dry fermented sausage (Poličan) dropped from 5.93 to 5.04 after the fermentation period. Seong et al ( 2016 ) also determined that the pH values of fermented sausages produced with soy protein decreased to 5.0–5.1. Ju et al ( 2016 ) reported a decrease in pH values of fermented pork sausages up to 21 d fermentation.…”
Section: Resultsmentioning
confidence: 98%
“…Lactobacillus sakei , L. plantarum and L. curvatus are generally the most isolated species from fermented sausages. An increase in the number of LAB in sausage prepared with soy sauce was reported during fermentation period and researchers stated that the LAB population reached about 7 log 10 cfu/g on the 5th day of fermentation (Seong et al 2016 ). Toldrá et al ( 2014 ) showed that LAB counts increased to 7–8 log cfu/g at the first 24–36 h of meat fermentation and remained stable during the rest of fermentation and storage period.…”
Section: Resultsmentioning
confidence: 99%
“…By day 9, the pH of WH was notably lower compared to the others ( p < 0.05). This may be due to the efficient fermentation abilities of W. hellenica [ 26 ].…”
Section: Resultsmentioning
confidence: 99%